Evaluation of Biofloc Technology Application on Water Quality and Production Performance of Red Tilapia Oreochromis sp. Cultured at Different Stocking Densities - . WIDANARNI; JULIE EKASARI; SITI MARYAM (Bogor Agricultural University, Indonesia, 2012)
This study evaluated the effect of biofloc technology (BFT) application on water quality and production performance of red tilapia Oreochromis sp. at different stocking densities. Three different fish densities were applied, i.e. 25, 50, and 100 fish/m3, and for each density there were Control (without external carbon input) and BFT treatments. Mixed sex red tilapia with an initial average body weight 77.89 + 3.71 g was cultured in 3 m3 concrete tanks for 14 weeks. Molasses was added on BFT treatments as the organic carbon source at a C/N ratio of 15. Control treatments of each density tested showed more fluctuated water quality parameters throughout the experimental period. The highest TAN and nitrite-nitrogen were observed in control treatment at a stocking density of 100 fish/m3 (3.97 mg TAN/L and 9.29 mg NO2-N/L, respectively). The highest total yield was observed in control treatment at the highest density treatment (43.50 kg), whereas the highest survival was obtained by BFT treatment at a density of 25 fish/m3 (97.78 + 0.77%). Total feed used in BFT was lower than that of control treatments in particular at 50 fish/m3 density (P < 0.05) suggesting that biofloc could be continuously harvested by the fish as other source of food.